PROKLITIK PRONOMINA PERSONA BAHASA TABA - Mujahid Taha (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study aims to find out the first, second, and third forms of personal prclitital pronouns of the Taba (BT) language. The method used is the method of data collection and data analysis. The data of this study are morphemes that contain proclitic elements attached to verbs (verbs), prepositions (preposition particles), and singular possessive nouns (nouns. The source of this research data is oral data that was told directly by BT native speakers in Waigitang Village, Pulau Makeang District, South Halmahera Regency, North Maluku Province. Based on the results of the study, it was found the BT verb with the first and plural personal pronouns, first person: k-, n-, (objects), and n- (human), first person plural: tit/ tat- and a-; the second person is singular and plural, the singular second person in the m-morpheme and the plural second persona in the morpheme h-; and the third third person in the i- morpheme, and the third person plural in the l- morpheme.